Board Committees, CEO Compensation, and Earnings Management - Christian Laux; Volker Laux (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2007)
We analyze the effect of committee formation on how corporate boards perform two main functions: setting CEO pay and overseeing the financial reporting process. The use of performance-based pay schemes induces the CEO to manipulate earnings, which leads to an increased need for board oversight. If the whole board is responsible for both functions, it is inclined to provide the CEO with a compensation scheme that is relatively insensitive to performance in order to reduce the burden of subsequent monitoring. When the functions are separated through the formation of committees, the compensation committee is willing to choose a higher pay-performance sensitivity as the increased cost of oversight is borne by the audit committee. Our model generates predictions relating the board committee structure to the pay-performance sensitivity of CEO compensation, the quality of board oversight, and the level of earnings management.
Keywords: M41; G34; L29; D73; K22; D23; 330; Corporate Governance; Executive Compensation; Earnings Management; Board Oversight; Aufsichtsrat; Corporate Governance; Vorstand; Vergütungssystem; Erfolgsrechnung; Bilanzpolitik; Theorie